2012
DOI: 10.4102/sajhivmed.v13i4.110
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for discordant immune response among HIV-infected patients initiating antiretroviral therapy: A retrospective cohort study

Abstract: Background. The therapeutic goal of antiretroviral therapy (ART) is sustained immune recovery and viral suppression. However, some patients experience poor CD4 cell count responses despite achieving viral suppression. Such discordant immune responses have been associated with poor clinical outcomes. Objective. We aimed to determine the prevalence of discordant immune response and explore associated factors in a retrospective cohort of patients attending 2 large public sector clinics, during the 6 months follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
3
12
2
Order By: Relevance
“…The bi-phasic CD4+ count response shown in our finding was also reported by other findings [ 18 , 19 ] as a rapid increase of memory CD4+ cells (a high CD4+ count slope) in the first several months after treatment initiation succeeded by a slow increase in naive CD4+ cells (smaller slope compared to the initial several months). The linear trend in CD4+ increment at early phase of of therapy became flat with minimal CD4+ gain latter after 18th month of treatment irrespective of the regimen used.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The bi-phasic CD4+ count response shown in our finding was also reported by other findings [ 18 , 19 ] as a rapid increase of memory CD4+ cells (a high CD4+ count slope) in the first several months after treatment initiation succeeded by a slow increase in naive CD4+ cells (smaller slope compared to the initial several months). The linear trend in CD4+ increment at early phase of of therapy became flat with minimal CD4+ gain latter after 18th month of treatment irrespective of the regimen used.…”
Section: Discussionsupporting
confidence: 91%
“…Immunologic response after 6 months of ART indicates a favourable clinical outcome in HIV-1 infected patients regardless of virologic response [ 20 ]. Several studies has reported that as many as 8–40% of patients on ART do not show a significant increase in CD4+ cell count despite viral suppression [ 18 , 21 , 22 ]. Our finding, in general, is almost consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result is supported by finding from a study conducted in Johannesburg, South Africa. 26 In most the case, anemic patients are more likely to have advanced immunosuppression and a higher rate of comorbidities which could impose a negative effect of response to ARV treatments. Evidence from other studies also shows anemia at ART initiation associated with increased mortality, disease progression (poor virologic response) and reduced quality of life.…”
Section: Discussionmentioning
confidence: 99%